Análise do processo de decisão de investimento em tecnologias WtE para resíduos sólidos urbanos: um estudo de caso - Lima, Maria Soares de (Universidade do Vale do Rio dos Sinos, 2021)
The management of MSW (Urban Solid Waste) adequately solves the challenges brought by MSW, as well as by recovering the value of these materials by WtE (Waste-to-Energy) technologies, it becomes a good option for a renewable energy source. However, the option of investing in these technologies are decisions made about many criteria established by managers, due to the complexity involved in MSW materials. In this context, this study proposes to serve as a guide so that it can support decision making on WtE technologies for the management of MSW, in a qualitative/quantitative approach. The result of the study pointed out and analyzed the criteria 15 criteria that can support the decision-making of the investment project in WtE technology for MSW. As well as presenting the assessment of the financial and economic viability of this project, pointing it as economically viable, with a result of the NPV (Net Present Value) of more than 7 million reais in the period and the IRR (Internal Rate of Return) of 9,10%, these projects are attractive in developing countries, and this project under study is a public-private partnership, so the issue of economic viability was assessed both from the point of view of municipal management and the concessionaire. Contributing to the development of these technologies in developing countries by the results brought here, as well as pointing out opportunities for consortia between municipalities and the generation of fuel generated from these, which can be a source of viability for these projects. Concluding with the viable results for these investment projects as well as the validation of the criteria that can support the decision process.
Keywords: Gerenciamento de RSU; Tecnologias WtE; Hierarquia de resíduos; Saúde pública; MSW management; WtE Technologies; Waste hierarchy; Public health; ACCNPQ::Engenharias::Engenharia de Produção